1976
DOI: 10.1007/bf01638344
|View full text |Cite
|
Sign up to set email alerts
|

Zur Pharmakokinetik von Azlocillin, einem neuen halbsynthetischen Breitspektrumantibiotikum

Abstract: Azlocillin, a new semisynthetic penicillin with a wide spectrum of antimicrobial activity and a member of the ureidopenicillin group, was administered to ten adults in a dosage of 2 g by intravenous bolus injection. The determination of antibiotic activity in serum and urine demonstrated an average concentration of 58.9 mug/ml after one hour, 28.1 mug/ml after two hours and 6.1 mug/ml after four hours. The total urinary excretion was 60% within six hours. The pharmacokinetic parameters were calculated for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

1977
1977
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 4 publications
2
5
0
2
Order By: Relevance
“…DISCUSSION In a previous study, Wirth et al (10) found serum concentrations of azlocillin nearly identical to those found in this investigation in 10 subjects with normal renal function given 2-g intravenous injections of the antibiotic. In their study the average half-life was 51.5 min, which does not differ significantly from our rates for subjects with normal renal function.…”
Section: Methodssupporting
confidence: 86%
“…DISCUSSION In a previous study, Wirth et al (10) found serum concentrations of azlocillin nearly identical to those found in this investigation in 10 subjects with normal renal function given 2-g intravenous injections of the antibiotic. In their study the average half-life was 51.5 min, which does not differ significantly from our rates for subjects with normal renal function.…”
Section: Methodssupporting
confidence: 86%
“…The pharmacokinetic data worked out in the present study are only limitedly compa rable to hitherto published ureidopenicillin reports, since the latter only describe serum concentration courses up to maximally 8 h, and an open 2-compartment model was generally taken as a basis [2,10,15,27]. Comparison of the serum concentration courses up to 8 h, however, yield findings parallel to those of the authors mentioned, and there is also good agreement with the Bay K data presented by Rohwedder and Morel [24], The high extrarenal elimination of Bay K apparently leads to a retardation of elimination with lower elimination con stants K10, a prolonged half-life and a larg er area under the curve in comparison to mezlocillin.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adults, the pharmacokinetic parameters are characterised by a small volume of distribution, and a variable but relatively high plasma clearance (Bergan & Michalsen 1979;Colaizzi et al 1986;Lode et al 1977;Wirth et al 1976) [table III]. In the study, in which intravenous azlocillin doses of 14.6, 29.3, and 73 mg/kg were administered to volunteers, there were dose-dependent pharmacokinetics (table III).…”
Section: Volunteersmentioning
confidence: 97%